Observations of biennial reproduction in Caribbean reef sharks ‘Carcharhinus perezi’ - Campbell, Beckah A.; Shipley, Oliver N.; Jones, Taeler R.; Gallagher, Austin J.; Sulikowski, James A. (Frontiers in Marine Science, 2024)
Effective management and conservation of threatened species biodiversity requires knowledge of reproductive biology, such as cyclicity, mode, and age at maturity. We combined reproductive endocrinology and in-situ ultrasonography to examine reproductive characteristics of female Caribbean reef sharks Carcharhinus perezi, a widely distributed, threatened marine predator which remains largely understudied throughout its range. Unique to this study was the opportunity to conduct longitudinal assessments of two individuals, recaptured across multiple seasons during sampling in The Bahamas. Within-individual, paired hormone analyses and in-situ ultrasounds of female sharks that were confirmed as either pregnant, non-pregnant, or reproductively active, suggest a biennial reproductive cycle for Carcharhinus perezi. This unique opportunity to assess the reproductive biology of the same individuals over time underscore the importance of repeated sampling for elucidating population reproductive cyclicity of highly mobile sharks in the wild.